The impact of radiological retroperitoneal lymphadenopathy on survival after cytoreductive surgery and hyperthermic intraperitoneal chemotherapy for colorectal peritoneal metastases. Issue 3 (March 2019) - van der Werf, L.R.; Wassenaar, E.; de Niet, A.; Lalezari, F.; Braam, H.J.; van Ramshorst, B.; Nederend, J.; de Hingh, I.H.J.T.; Kok, N.F.M.; Aalbers, A.G.J.
Abstract: Objectives: To investigate the impact of retroperitoneal lymphadenopathy (RPLP) on pre-operative CT scan on overall survival (OS) and disease-free survival (DFS) after cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (CRS-HIPEC) for peritoneal metastases (PM) of colorectal cancer. Background: In patients with PM enlarged retroperitoneal lymph nodes (RPLP) are usually considered extra-regional lymph node metastases and therefore these patients may be excluded from CRS-HIPEC. This is a clinical dilemma since it is often hard to obtain histology from these nodes. Methods: In this multicenter, retrospective study all consecutive patients with colorectal PM treated with CRS-HIPEC between 2004 and 2013 were included. The preoperative CT-scan was re-analyzed for the presence of RPLP based on the radiological appearance of enlarged lymph nodes. Outcomes were OS and DFS. Kaplan-Meier methods and Cox regression modeling were used to analyze the impact of RPLP on OS and DFS. Results: In 25 of 401 patients (6.1%) RPLP was observed on the preoperative CT-scan. Patient, tumor and surgical characteristics did not statistically significantly differ between groups with and without RPLP. After a median follow-up of 46 months, the one-, three- and five-year survival was 80%, 59%, 38% and 90%, 50%, 36% in the group with and without RPLP respectively. Median OS (47 vs. 35 months, logrank: p = 0.70) and median DFS (14 vs. 15 months, logrank: p = 0.81) did not statistically significantly differ between groups. In multivariable analysis, RPLP did not significantly influence survival. Conclusion: Enlarged retroperitoneal lymph nodes on a pre-operative CT-scan should not automatically exclude patients from CRS-HIPEC.